Effects of a school-based prevention programme on smoking in early adolescence: a 6-month follow-up of the 'Eigenständig werden' cluster randomised trial. Issue 1 (21st January 2014) - Isensee, Barbara; Hansen, Julia; Maruska, Karin; Hanewinkel, Reiner
Abstract : Objectives: To test the effects of a school-based prevention programme on students' smoking-related behaviour, attitudes and knowledge 6 months after implementation over 2 school-years has ended. Design: Two-arm prospective cluster randomised controlled trial with a follow-up survey 6 months after end of programme implementation, that is, 26 months after baseline. Setting: 45 public secondary schools from four federal states in Germany (Bremen, Hesse, North Rhine-Westphalia, Schleswig-Holstein). Participants: A total of 3444 students from 172 classes with a mean age of 10.37 years (SD=0.59) and 47.9% girls at baseline. Analysis sample with follow-up up data merged to baseline data comprises 2513 datasets (73%). Intervention: 'Eigenständig werden 5+6', a school-based prevention programme for grades 5 and 6 to enhance substance-specific and general life skills, consisting of 14 units (à 90 min) and two workshops (4–6 h) being taught over a time period of 2 school-years by trained teachers. Outcome measures: Lifetime and current smoking, incidence of smoking in baseline never smokers, smoking-related knowledge, attitudes, perceived norms of smoking and self-efficacy to refuse cigarette offers were assessed in students. Results: 6 months after the end of programme implementation, students of intervention classes showed significantly lower rates for lifetime smoking (adjusted OR=0.63; 95% CI 0.41 to 0.96; p=0.026) and incidence of smoking (adjusted OR=0.66; 95% CI 0.43 to 1.00; p=0.047), a higher increase of smoking-related knowledge (adjusted β=9.38; 95% CI 6.73 to 12.04; p<0.001) and a greater change in attitudes towards a more critical perception of risks and disadvantages of smoking (adjusted β=0.10; 95% CI 0.03 to 0.16; p=0.002). No group differences were found for current smoking, perceived norms of smoking and self-efficacy to refuse cigarette offers. Conclusions: Participation in the school-based prevention programme 'Eigenständig werden 5+6' may have small effects on smoking behaviour and attitudes and a moderate effect on smoking-related knowledge. Trial registration: Current Controlled Trials ISRCTN99442407